Reimagining the Vernacular: Exploring Linguistic Hybridity in Postcolonial English Literature through Rushdie, Achebe, and Díaz - Shaaban Sulaiman Sadeeq (QALAAI ZANIST JOURNAL, 2024)
This study delves into the captivating phenomenon of linguistic hybridity in postcolonial English literature, focusing on the works of Salman Rushdie's Midnight’s Children Chinua Achebe's Things Fall Apart and Junot Díaz's The Brief Wondrous Life of Oscar Wao By examining these authors' skillful blending of languages, dialects, and cultural elements, this research seeks to understand how linguistic fusion challenges traditional boundaries of the English language and sheds light on the complexities of postcolonial identities. Central to this investigation are questions surrounding the authors' use of code-switching, multilingualism, and cultural integration to convey themes of identity, belonging, and cultural negotiation. Furthermore, this study explores the role of linguistic choices in crafting distinctive literary voices and styles that resonate with multicultural contexts. Ultimately, this research highlights the potential for linguistic hybridity to serve as a means of defying societal domination and examines its manifestation in these influential narratives. By offering a comprehensive analysis of linguistic fusion within these seminal works. This research advances our knowledge of how language in postcolonial English literature can alter.